Characterization of expanded polystyrene waste as binder and coating material. (June 2022) - Gutierrez-Velasquez, Elkin I.; Monteiro, Sergio Neves; Colorado, Henry A.
Abstract: The growth of consumer culture entails a series of harmful results for the different natural environments, one of these evils being the high rate of waste generation, an example, expanded polystyrene (EPS) today has become a major problem due to the high rates of generation of this type of waste. This study presents the results of EPS waste characterization, obtained by the degradation of EPS with solvent mixtures of acetone and ethyl acetate in different proportions, for possible use as an asphalt adhesive. For the characterization of these EPS waste mixtures, stress tests of the asphalt adhesive were carried out and they were complemented with tests of resistance to cutting, stickiness, rheology and thermogravimetric. The results obtained in this work show that the EPS waste obtained by dissolution with acetone and ethyl acetate solvent mixtures, present greater mechanical resistance, although these wastes have a higher apparent viscosity and a faster drying as it increases the acetone content present in the solvent. Tests showed that this material could be used as an asphalt coating film or adhesive binder. Highlights: An evaluation of the EPS waste obtained by degradation with commercial solvents was carried out. The EPS degradation process, using solvents, to obtain wastes of different characteristics is described. The influence of the percentages of acetone and ethyl acetate on the characteristics of the waste obtained are analyzed. The results of rheological, mechanical and thermogravimetric characterizations are presented.